Preparation of Xenopus tropicalis whole chromosome painting probes using laser microdissection and reconstruction of X. laevis tetraploid karyotype by Zoo-FISH - Krylov, Vladimir; Kubickova, Svatava; Rubes, Jiri; Macha, Jaroslav; Tlapakova, Tereza; Seifertova, Eva; Sebkova, Natasa (Chromosome research, 2010)
Laser microdissection was used for the preparation of whole chromosome painting probes in Silurana (Xenopus) tropicalis. Subsequent cross-species fluorescence in situ hybridization (Zoo-FISH) on its tetraploid relative Xenopus laevis revealed persistence of chromosomal quartets even after 50-65 million years of separate evolution. Their arrangement is in a partial concordance with previous experiments based on similarity of a high-resolution replication banding pattern. Further support for an allotetraploid origin of X. laevis was given by hybridization with a probe derived from the smallest X. tropicalis chromosome (Xt10). Here, pericentric areas of both arms of Xl 14 and 18 were stained, indicating intrachromosomal rearrangements. The positions of signals were not in agreement with the chromosomal quartets revealed by painting probes Xt 8 and 9 (Xl 11 + 14 and Xl 15 + 18, respectively). This suggests that both X. tropicalis chromosomes underwent non-reciprocal translocation of Xt10 separately in at least two different ancient ancestors. In addition, the observed translocation events could explain the origin of individuals with 18 chromosomes in diploid karyotypes, probably extinct after the genesis of the allotetraploid X. laevis (2n = 36).
Keywords: Chromosome Banding; Xenopus; biologická evoluce; mikrodisekce; DNA sondy; hybridizace in situ fluorescenční; chromozomy; karyotypizace; Biological Evolution; Karyotyping; Xenopus laevis; cytogenetické vyšetření; DNA Probes; In Situ Hybridization, Fluorescence; zvířata; Chromosomes; pruhování chromozomů; Translocation, Genetic; translokace genetická; Microdissection; Cytogenetic Analysis; Animals